Coffee cultural landscape didactic material for rural schools (2020)
The hotbed Design Culture research group, Technology and Culture, in 2009, began the research: Material Culture Coffee teachers led by Yaffa Nahir Gomez Barrera, which initially established a state of the art, then continued to work until 2012, establishing a valuation of the objects that are part of the coffee culture, which led to the approach of different needs for preserving it. Thus, there is an opportunity to develop a project focused on the development of training materials for the child population in rural schools of Risaralda's department.